Taffy's foal - Bialk, Elisa (Houghton Mifflin, 1949)
When ten-year-old Nancy leaves her grandmother's Kentucky farm and her horse Taffy to live with her father and her new mother in Chicago, she must learn to overcome her shyness with schoolmates, feel that she belongs at home, and to accept the death of her mare as well as rejoice at the birth of a foal.